Pemaafan dan Subjective Well-Being Pada Remaja Suku Timor di NTT yang Hamil di Luar Nikah - Ndoloe, Angel Lidiandri Mutiara; Huwae, Arthur (STIKES Yayasan RS.Dr.Soetomo, 2024)
Experiencing pregnancy problems as an adolescent is not easy in everyday life. Likewise, Timornese adolescents who are pregnant out of wedlock have to accept the condition of extramarital pregnancy with various impacts. Therefore, forgiveness is needed in Timornese adolescents who experience pregnancy out of wedlock to improve their subjective well-being, so that they can get through and live their lives. The purpose of this study was to determine the relationship between forgiveness and subjective well-being of Timornese adolescents in NTT who are pregnant out of wedlock. The research method used was quantitative correlation. A total of 104 Timornese adolescents who are pregnant out of wedlock were used as participants in this study using purposive sampling technique. The scales used in this study were Transgression-Related Interpersonal Motivations (TRIM-18), Satisfaction with Life Scale (SWLS), and Positive Affect Negative Affect Scale (PANAS). The results of the Pearson Correlation hypothesis test value is -0.157 with sig.=0.056 (p>0.05), which means that the hypothesis is rejected. This indicates that forgiveness is not one of the factors associated with subjective well-being in Timornese adolescents who are pregnant out of wedlock. This means that when there is an increase or decrease in forgiveness, there is no relationship with subjective well-being.